Unveiling the Performance Symphony of Iron Fluoride Cathodes in Advanced Energy Storage Devices - Dhivyadharshini; Raj, Sindhu S.; Arpita, B. J.; Vishnumurthy, K. A. (The Korean journal of chemical engineering, 2024)
Increasing the storage capacity of portable electronic storage devices is one example of how energy storage and conversion have recently emerged as key research subjects for addressing social and environmental concerns. Metal fluoride cathodes have recently received a lot of attention as potential components for high-performance lithium batteries. These cathodes have unique electrochemical properties that make them suitable for energy storage applications. The research looks into the electrochemical properties of numerous metal fluorides, including transition metal fluorides and rare earth metal fluorides. The study finishes by emphasising metal fluoride cathode applications in portable electronics, electric cars and grid energy storage.